Investigação do processamento das proteínas do sistema calicreína-cinina plasmático na interação com células endoteliais - Assis, Mirian Coelho de [UNIFESP] (2019)
Endothelial cells (ECs) correspond to the coating of both vessels the lymphatic vessels and constitute the inner layer of these glasses These cells are flattened epithelial and distributed in monolayer presenting great heterogeneity, since they differ in size, length and height, shape and number of stored vesicles, and this is related to the caliber of the blood vessel or a tissue (Aird, 2007; Dela-Paz et al., 2009). The endothelium is considered an endocrine organ capable of producing and secreting a variety of chemicals that control clotting, tonus and plasma levels of endogenous mediators and lipoproteins (Carvalho et al., 2005). However, it is also involved in a number of pathological conditions, such as atherosclerosis and cancer (Dela-Paz et al., 2009), and in diffuse intravascular coagulation the endothelium is the interface between inflammation and inappropriate activation of the coagulation system (Kato, 2014). The endothelium exerts several functions as regulation of the inflammatory response and inhibition of cell proliferation and migration. The release of substances such as vasodilators and vasoconstrictors conserve laminar blood flow, preserving the fluidity of the plasma membrane, creating mechanisms anticoagulants. Vasodilators such as nitric oxide, bradykinin and adenosine, in channels of K + dependent on ATP, its activation by vasodilators, associated with hyperpolarization of the membrane, the closure of the K + , act on the cells of the smooth muscle cells present in the tunica media of arterioles resulting in reduced blood flow resistance and decreased blood pressure. On the other hand vasoconstrictors include endothelin and angiotensin II which promote smooth muscle contraction and increase the (Baxter et al., 2006), and the effect of the antihypertensive effect on the blood pressure (Baxter et al. The functions exerted by the endothelium regulate cell-cell interactions and cell-matrix, the expression and presence of membrane-bound receptors being associated with numerous molecules including proteins, carrier particles of lipids, metabolites and hormones, and glycosaminoglycan sugars (Rajendran et al., 2013, Muller, 2013).